2012
DOI: 10.1371/journal.pone.0037078
|View full text |Cite
|
Sign up to set email alerts
|

Non-Uniform Distribution Pattern for Differentially Expressed Genes of Transgenic Rice Huahui 1 at Different Developmental Stages and Environments

Abstract: DNA microarray analysis is an effective method to detect unintended effects by detecting differentially expressed genes (DEG) in safety assessment of genetically modified (GM) crops. With the aim to reveal the distribution of DEG of GM crops under different conditions, we performed DNA microarray analysis using transgenic rice Huahui 1 (HH1) and its non-transgenic parent Minghui 63 (MH63) at different developmental stages and environmental conditions. Considerable DEG were selected in each group of HH1 under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(23 reference statements)
0
8
1
Order By: Relevance
“…The transcriptomic comparisons result indicated that the expressed levels of all these six genes can be regulated by biotic or abiotic stresses in previous studies. The result of study (GSE33204) indicated that Os02g0527300 (OsHsfA3) and Os03g0335200 (OsWRKY44) showed upregulation, and showed downregulation in 30-day-old leaves of rice after 6H high temperature treatment [39]. However, these three genes did not show alternated expression level in WT induced by heat stress in our study, which might be attributed to the different genotype, development stage, tissue or treatment condition.…”
Section: Atplc9 Confers Heat Tolerance To Monocotyledons As Well As Dcontrasting
confidence: 55%
“…The transcriptomic comparisons result indicated that the expressed levels of all these six genes can be regulated by biotic or abiotic stresses in previous studies. The result of study (GSE33204) indicated that Os02g0527300 (OsHsfA3) and Os03g0335200 (OsWRKY44) showed upregulation, and showed downregulation in 30-day-old leaves of rice after 6H high temperature treatment [39]. However, these three genes did not show alternated expression level in WT induced by heat stress in our study, which might be attributed to the different genotype, development stage, tissue or treatment condition.…”
Section: Atplc9 Confers Heat Tolerance To Monocotyledons As Well As Dcontrasting
confidence: 55%
“…T2A‐1 expresses a synthetic cry2A gene and T1C‐19b expresses a synthetic cry1C gene, with expression of both driven by the maize ubiquitin promoter (Wang et al ., ; Li et al ., ; Li et al ., ). Huahui 1 expresses a fused cry1Ab/Ac gene under the control of rice actinI promoter (Liu et al ., ). Minghui 63 is an elite indica restorer line for cytoplasmic male sterility in China, and served as non‐transgenic control in this study.…”
Section: Methodsmentioning
confidence: 97%
“…Previous studies have shown that comparisons of differences in agronomic traits ( Xia et al, 2011 ; Wang et al, 2012a ; Li et al, 2013 ; Jiang et al, 2016 ), nutritional composition ( Wang et al, 2012b ; Jian et al, 2014 ; Jiang et al, 2018 ; Takeda et al, 2019 ), environmental adaptability ( Jiang et al, 2018 ; Wang et al, 2019 ; Park et al, 2019 ), gene transcription, protein expression, and metabolite levels ( Liu et al, 2012 ; Liu Y. et al, 2015 ; Fu et al, 2019 ; Peng et al, 2019 ) among transgenic crops and their parents are important means and strategies for confirming and excluding the unintended effects of transgenic crops, in addition to facilitating any safety evaluations. However, the molecular mechanisms of underlying the unintended effects observed in transgenic crops are unclear.…”
Section: Discussionmentioning
confidence: 99%